The factors that influence to the effectiveness of training program at TM SME, TM Berhad / Wan Farzana Wan Musa - Wan Musa, Wan Farzana (2011)
Training program is designed to help new and existing resellers adjust to work with successfully. In addition, they include the formal ongoing efforts of organizations to improve the performance of their employees through a variety of methods and programs. This paper attempts to identify the significant factors that influence training effectiveness. Four objectives was constructed which are first, identify what is the level of effectiveness of training conducted by TM SME, second is to identify what are the factors influence to the effectiveness of training conducted by TM SME, third is to determine most influence factors towards the effectiveness of training conducted by TM SME and fourth is to suggest the ways TM SME can increase and maintain its effective in the training conducted. The respondents of this study are the partners who came for training conducted by TM SME. 66 questionnaires were distributed in order to complete the purpose of study. The researcher used probability sampling, while telephone interview and personal interview were used as the method of collecting data. At the end of the research, the researcher found the level of training to be positive, which each of the factors mentioned as the independent variables having positive results toward the effectiveness of training conducted by TM SME.